Mechanistic insights into dye adsorption on chitosan-functionalized bentonite: synergizing experiments and computational study - Rachid Et-tanteny; Ibrahim Allaoui; Rachid Haloui; Souad Elkhattabi; Khalid Draoui; Karim El Khadiri (Chemical Physics Impact, 2025)
Natural Moroccan bentonite (Bnt) exhibited a high adsorption capacity for crystal violet (CV, a cationic dye), reaching 157.37 mg/g. Conversely, its affinity for methyl orange (MO, an anionic dye) was limited (20.14 mg/g). However, the synthesized bentonite-chitosan composite (Bnt-Cs) features protonated amine groups, which enhance electrostatic and hydrogen-bond interactions, increasing the adsorption of MO dye by 76.65%. The kinetic data revealed that MO adsorption followed the pseudo-first-order (PFO) model, whereas CV adsorption was better described by the pseudo-second-order (PSO) model. These two models are governed by distinct diffusion mechanisms. Moreover, the adsorption isotherms for both dyes aligned well with the Freundlich model. Additionally, the Density Functional Theory (DFT) calculations indicated that CV’s narrower HOMO–LUMO gap and higher molecular softness were consistent with its enhanced reactivity and stronger interaction with the adsorbent. Furthermore, the molecular dynamics (MD) simulations confirmed the spontaneous, physically driven nature of the adsorption process. The close agreement between computational predictions and experimental data provides robust validation for the proposed adsorption mechanisms, offering clear mechanistic insights into dye adsorption processes.